Online Learning Through The RADEC Model to Increase HOTS of Elementary School Students in The Time of The Covid-19 Pandemic - Pratama, Yoga Adi; Dewi, Laksmi (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2022)
During the Covid-19 pandemic, thinking skills-oriented learning has not been implemented properly, the impact of student HOTS is getting lower. The purpose of this study is to increase the HOTS of elementary school students during the Covid-19 pandemic through the RADEC learning model. The research was conducted at SDN Harapan 1 Cimahi City. The research methodology uses classroom action research. Data collection techniques used are tests and observations. Data analysis used comparative analysis techniques and qualitative analysis. The results showed that there were only 2 students in the pre-cycle data that obtained the